The Iron Deficiency-Regulated Small Protein Effector FEP3/IRON MAN1 Modulates Interaction of BRUTUS-LIKE1 With bHLH Subgroup IVc and POPEYE Transcription Factors - Lichtblau, Daniela M.; Schwarz, Birte; Baby, Dibin; Endres, Christopher; Sieberg, Christin; Bauer, Petra (Frontiers in Plant Science, 2022)
In light of climate change and human population growth one of the most challenging tasks is to generate plants that are Fe-efficient, resilient to low Fe supply and Fe-biofortified. For such endeavors, it is crucial to understand the regulation of Fe acquisition and allocation in plants. One open question is how identified Fe-regulatory proteins comprising positive and negative regulators act together to steer Fe homeostasis. bHLH transcription factors (TFs) belonging to the subgroups IVb and IVc can initiate a bHLH cascade controlling the -Fe response in roots. In Arabidopsis thaliana, the -Fe-induced genes are sub-divided into several gene co-expression clusters controlled by different sets of TFs. Some of the co-expressed genes encode regulatory E3 ligase proteins BRUTUS (BTS)/BTS-LIKE (BTSL) and small proteins belonging to the group of FE UPTAKE-INDUCING PEPTIDE/IRON MAN (FEP/IMA). Recently, it was described that FEP1/IMA3 and FEP3/IMA1 proteins inhibit the repression of bHLH factors by BTS. We had postulated that -Fe-regulated co-expression clusters provide new information about regulatory protein interaction complexes. Here, we report a targeted yeast two-hybrid screen among 23 proteins of the -Fe response. This identified a novel protein interactome involving another E3 ligase, namely BTSL1, basic helix-loop-helix (bHLH) protein POPEYE (PYE) and transcription factors of the subgroup IVc as well as FEP3/IMA1. Because of the difficulty in stable BTSL1 protein expression in plant cells, we used a yeast two hybrid-based deletion mapping, homology modeling and molecular docking, to pinpoint interaction sites in BTSL1 and FEP3/IMA1. bHLH IVc TFs have similar residues at their C-terminus as FEP3/IMA1 interacting sites. FEP3/IMA1 attenuated interaction of BTSL1 and bHLH proteins in a yeast three-hybrid assay, in line with physiological data pointing to enhanced Fe acquisition and allocation in FEP3/IMA1 overexpression and btsl1 btsl2 mutant plants. Hence, exploiting -Fe-induced gene co-expression networks identified FEP3/IMA1 as a small effector protein that binds and inhibits the BTSL1 complex with PYE and bHLH subgroup IVc proteins. Structural analysis resolved interaction sites. This information helps improving models of Fe regulation and identifying novel targets for breeding of Fe-efficient crops.